Post puerulus of scalloped spiny lobster, Panulirus homarus (Linnaeus 1758) rearing in floating net cage with different artificial diet. Issue 1 (June 2020) - Slamet, B; Rusdi, I; Giri, A; Haryanti,
Abstract: Scalloped spiny lobster ( Panulirus homarus) is an export commodity and high economic value in Asian-Pacific markets. The purpose of this study was to determine the best artificial feed for scalloped spiny lobster nursery in floating net cage. The nursery was conducted using 9 floating net cage 1 × 1 × 1 m in size with three treatments and 3 replicates. Three different artificial diets were used as treatments, i.e.: A, commercial pellet for grouper, with higher protein level (53.56%) but lower stability, less durable in water and will break within 3-4 hours after administration; B, commercial pellet for shrimp, with lower protein level (33.07%) but higher stability, will break within 10-12 hours after administration and C: pellet formula IMRAD Gondol, with middle protein level (46.51%) and higher stability, will break within 10-12 hours after administration.The post puerulus with total length 2.1±0.18 cm and body weight 0.28±0.04 g was reared at density of 100 ind/cage. A complete random design was used as an experiment design and analyzed by ANOVA. Feeding were given twice a day, 5% of biomass/day. The study was conducted for 4 months. The sampling of survival rate, total length and body weight were conducted every month and total haemocyte on the end of experimentwas measured. The result showed that there was significant different (P<0.05) for survival rate, but not significant different (P>0.05) among treatments for growth of total length and body weight. The best survival rate was on treatment C (39.0%), followed by treatment A (29.7%): and treatment B (16.7%). The number of haemocyte was almost the same between treatments with total haemocyte 250-285 x 10 4 per ml. From these results it can be concluded that pellet formula IMRAD Gondol can be used for rearing of scallop spiny lobster post puerulus.